Construction Product Quality Improvement with Applying Production Problems Analysis - Stasiak-Betlejewska, Renata (Manufacturing Technology Journal, 2015)
The study and analysis of the production process of the aluminum joinery allow identyfing factors significantly affecting the product quality. The main factor is undoubtedly the experience of employees, skills and the knowledge acquired during training and the aluminium ironworks. To improve construction aluminium product quality, production areas with identified nonconformities are the object of the analysis. Detection of nonconformities is an important element in this type of post-operative control process. It is recommended mainly to control the cutting sections, folding and crimping. The reliability increase performed on these operation positions significantly affects the product quality. The modernity level of the machinery has also significant meaning mainly for the process productivity.
Keywords: Alluminium Joinery; Quality; Production Control; Value Engineering